2016
DOI: 10.1158/1940-6207.capr-15-0276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Ursodeoxycholic Acid in Barrett's Esophagus Patients

Abstract: Prior research strongly implicates gastric acid and bile acids, two major components of the gastroesophageal refluxate, in the development of Barrett’s esophagus (BE) and its pathogenesis. Ursodeoxycholic acid (UDCA), a hydrophilic bile acid, has been shown to protect esophageal cells against oxidative stress induced by cytotoxic bile acids. We conducted a pilot clinical study to evaluate the clinical activity of UDCA in patients with BE. Twenty-nine BE patients received UDCA treatment at a daily dose of 13–15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 29 publications
(32 reference statements)
0
29
0
3
Order By: Relevance
“…Banerjee et al. [155] found a significant increase in UDCA content (from 18 to 93% of the total BA content) in gastric fluid over the 6‐month treatment period with 13–15 mg/kg of UDCA daily and a decrease in the content of other generally toxic BAs (CDCA, DCA, CA, LCA). These findings were also confirmed by Bozikas et al.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Banerjee et al. [155] found a significant increase in UDCA content (from 18 to 93% of the total BA content) in gastric fluid over the 6‐month treatment period with 13–15 mg/kg of UDCA daily and a decrease in the content of other generally toxic BAs (CDCA, DCA, CA, LCA). These findings were also confirmed by Bozikas et al.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Unfortunately, in 29 patients who took oral UDCA, markers of oxidative DNA damage, cell proliferation, and apoptosis (as assessed by immunohistochemical staining) did not change. 91 Gastric acid represents a genotoxic stress as it induces double-strand DNA breaks in BE cells and patient tissues. 92 Gastric acid can activate oncogenic signaling pathways, such as ERK and p38MAPK, and silence tumor suppressor genes, such as p16.…”
Section: Chemopreventive Effects Of Ppis In Barrett's Esophagusmentioning
confidence: 99%
“…Ursodeoxycholic-acid supplementation has been hypothesized to alter the acid and bile composition of gastroesophageal refluxate and its use in preclinical studies has shown reduced rates of EAC in a rat model of BE [ 72 ]. However, a non-randomized pilot study of 29 patients with BE showed altered bile-acid composition after 6 months of ursodeoxycholic-acid supplementation but no change in the primary study endpoint of altered tissue biomarkers indicative of oxidative damage and apoptosis [ 73 ].…”
Section: Candidate Chemoprevention Therapies For Esophageal Adenocarcmentioning
confidence: 99%